Niemiecka polityka okupacyjna na Litwie w latach 1941–1944. Podsumowanie - Christoph Dieckmann (Zagłada Żydów)
The article regards German Occupation Policy in Lithuania 1941–1944. The author integrates the context of war and warfare – with their needs for mobilization, stability, food and labor – into the picture. He clearly shows how each of these fields of politics was coined by antisemitism, which was central for all Nazi policies. The author integrates multiple perspectives of perpetrators, bystanders and victims as well, emphasizing specific Lithuanian political programs, which enabled certain Lithuanian political groups to join partly national-socialist policy.